Towards uncertainty in dimensional metrology of surface features for advanced manufacturing - Musso, Giuseppe; Senin, Nicola; Galetto, Maurizio; Leach, Richard K. (2016)
In previous work, an original approach was developed for the dimensional characterisation of surface features on parts and test artefacts, aimed at supporting researchers involved in the study of advanced manufacturing processes. In the approach, methods and algorithms from image processing, coordinate metrology, surface metrology and reverse engineering are merged into an original framework for feature identification, extraction and dimensional characterisation, starting from areal topography data. With the ultimate goal of associating uncertainty to the results obtained in dimensional characterisation, this paper focuses on specifically investigating reproducibility and repeatability of dimensional characterisation results obtained on a test dataset consisting of a step-like feature manufactured by material jetting.